Resistance fluctuations in amorphous Cr74Fe26 films - (:unkn) unknown (ELSEVIER SCIENCE BV, 1998)
Magnetoresistance measurements Delta rho/rho have been carried out on an amorphous Cr74Fe26 film in the temperature range of 4-120 K in a magnetic field up to 120 kOe. We observed that the isotropic component of the magnetoresitance at low temperatures first decreases with increasing field due to the decrease in the spin fluctuations (negative mag magnetoresistance), goes through a minimum at a certain field value, H-c and then starts to increase (positive magnetoresistance) as the magnetic field is further increased. As the temperature increases. H-c, shifts ro a higher field and the magnetoresistance on both sides of this field (negative and positive magnetoresistance) decreases. The magnetoresistance becomes almost zero at temperatures between 10-16 K. However, as the temperature is further increased, the magnetoresistance starts to increase again. This overall behaviour with the resistivity data have been interpreted successfully in terms of localization effects. We have also observed huge oscillations in the resistivity at low frequencies (7-70 mHz) in the temperature range where Delta rho/rho becomes weaker. Starting with the temperature at about T = 15 K, the amplitudes of these oscillations reduce with both increasing and decreasing temperatures. However, the frequencies of these oscillations increase with decreasing temperature. No detectable oscillation in the resistivity has been observed at temperatures below T = 8 K and above T > T-c (the Curie temperature, T-c = 43.8 K). We have no full explanation for this phenomenon, however, it is tempting to ascribe it to some kind of spin density wave. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: amorphous systems : TM alloys; Anderson localization; magnetoresistance : amorphous alloys